Energy state of InGaAs quantum dots on SiO(2)-patterned vicinal substrate - Kim, Hyo Jin (Springer, 2012)
The optical properties of In(0.8)Ga(0.2)As self-assembled quantum dots (SAQDs) grown on GaAs wire structures formed by utilizing SiO(2)-patterned exact and 5°-off (001) GaAs substrates have been studied with micro-photoluminescence (μ-PL). Single PL peak was occurred for In(0.8)Ga(0.2)As SAQDs grown on SiO(2)-patterned exact (001) GaAs, whereas double PL peaks were showed for SAQDs grown on 5°-off (001) GaAs substrates as the width of the opening windows increased. The power-dependent μ-PL spectra show that the first and second peaks of these double peaks were originated from the well-defined ground and excited state, respectively. These results demonstrated that In(0.8)Ga(0.2)As SAQDs selectively grown by utilizing SiO(2)-patterned 5°-off (001) GaAs substrates have well-defined zero-dimensional quantum states.